Mix proportion and preparation method for preparing tunnel synchronous grouting slurry by using shield construction spoil in soft soil area
By optimizing the mixing ratio of grouting materials, using high-quality, environmentally friendly multi-particle-grade steel slag and soft soil special gelling materials, the problems of poor fluidity, high water excretion rate and insufficient mechanical properties in shield construction in soft soil areas are solved, and efficient, stable and safe grouting effect is achieved.
Patent Information
- Application Number
- CN202411883346.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional shield end grouting materials have problems such as poor fluidity, high water excretion rate and insufficient mechanical properties in shield construction in soft soil areas, which affect the grouting effect and tunnel stability.
By optimizing the mix ratio, high-quality and environmentally friendly multi-particle-grade steel slag, soft soil special gelling materials and water are used to prepare excellent performance of shield end grouting materials. The specific ratio is 20%-30% of multi-particle size graded steel slag, 30%-50% of slag, 8.01%-15% of soft soil special gelling materials, and 22.2%-31.49% of water.
It improves the slump and flowability of the grouting material, facilitates construction; controls the water excretion rate, ensures the stability of the grouting material; enhances the unlimited compressive strength, improves the mechanical properties of the grouting material, and ensures the stability and safety of the tunnel.
Smart Images

Figure CN119707415A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shield construction, and in particular to a mix ratio and a preparation method thereof for preparing tunnel synchronous grouting slurry by utilizing abandoned soil from shield construction in soft soil areas. Background Art
[0002] Shield construction is one of the important methods in modern tunnel and underground engineering construction. During the tunneling process, the shield machine forms a stable support structure by grouting the shield tail, filling the gap between the tunnel and the surrounding rock, and preventing ground settlement and tunnel deformation. The performance of the shield tail grouting material directly affects the effect of shield tunneling and the quality of the tunnel.
[0003] Traditional shield tail grouting materials usually use cement slurry or a mixture with a certain proportion of clay, sand, etc. However, these traditional materials have some problems in practical applications. For example, poor fluidity and operability. Traditional grouting materials have a low slump and poor fluidity, making it difficult to fill into the tiny gaps between the tunnel and the surrounding rock, affecting the grouting effect. Another problem is the high water seepage rate. Traditional grouting materials are prone to water seepage during long-term construction, resulting in a decrease in the uniformity and stability of the slurry, affecting the grouting quality. Another problem is the lack of mechanical properties. The unconfined compressive strength of the grouting material is low, and it cannot provide sufficient support, affecting the stability and safety of the tunnel.
[0004] High-quality and environmentally friendly multi-particle size graded steel slag is an industrial waste that contains rich calcium, iron, silicon and other components, and has good cementing properties and mechanical strength. In line with national environmental protection standards, it uses multi-particle size composites to form a composite framework with soft soil curing agents, improves the physical and chemical framework and reaction, and forms high-quality grouting materials. The customized "soft soil special cementing material" is a mineral powder-based soil hardener. Taking Baowu blast furnace slag powder (GGBS) as the main raw material, using the characteristics of containing Cao, SiO2 and Al2O3 as the main components, using physical + chemical excitation cementing materials as the basic technical route, it overcomes the shortcomings of traditional solidified soil, such as the difficulty of continuous distribution of hydration products, low early strength, and insufficient durability, which can greatly improve the engineering properties of soil. High-quality and environmentally friendly multi-particle size graded steel slag is mixed with soil and soft soil special cementing materials (customized), and by adjusting the mix ratio, a shield tail grouting material with excellent performance can be prepared. Reasonably proportioned, high-quality, environmentally friendly, multi-size gradation steel slag slurry has good fluidity, can effectively fill the gap between the tunnel and the surrounding rock, and improve the grouting effect. The high-quality, environmentally friendly, multi-size gradation steel slag slurry has a low water seepage rate, can maintain the uniformity and stability of the slurry, and ensure the grouting quality. The high-quality, environmentally friendly, multi-size gradation steel slag slurry has a high unconfined compressive strength, can provide sufficient support, and ensure the stability and safety of the tunnel. Therefore, studying and optimizing the mix ratio of grouting materials is of great significance to improving the shield construction efficiency and engineering quality. Summary of the invention
[0005] The present invention provides a mix ratio and a preparation method for preparing tunnel synchronous grouting slurry using abandoned soil from shield construction in soft soil areas. The mix ratio is optimized through experimental data to improve the slump, water bleeding rate and unconfined compressive strength of the abandoned soil, thereby ensuring good performance of the grouting material in shield construction.
[0006] The purpose of the present invention is achieved by the following technical solutions:
[0007] A mix ratio for preparing tunnel synchronous grouting slurry using abandoned soil from shield construction in soft soil areas includes the following components in weight percentage: multi-size graded steel slag: 20%-30%, slag: 30%-50%, soft soil special cementitious material: 8.01%-15%, and water: 22.2%-31.49%.
[0008] A method for preparing a mix ratio of tunnel synchronous grouting slurry using spoil from shield construction in soft soil areas, comprising the following steps: drying the slag, grinding it into fine powder, mixing it with multi-size graded steel slag and soft soil special cementitious material (customized) according to the mix ratio, and then putting it into a mixer for stirring. After stirring evenly, continue stirring and add water to the mixer according to the mix ratio until the slurry is stirred evenly.
[0009] The advantages of the present invention are that the slump and fluidity of the shield tail grouting material in soft soil areas are improved, which is convenient for construction; the water seepage rate is controlled to ensure the stability of the grouting material; the unconfined compressive strength is improved, and the mechanical properties of the grouting material are enhanced. In addition, the mixed slag mix ratio has significant environmental advantages. It effectively absorbs the slag that was previously considered as engineering waste and would cause environmental pollution, reducing the accumulation and pollution of waste. It also makes full use of the gelling properties of high-quality and environmentally friendly multi-particle size graded steel slag, converts industrial waste into valuable resources, and promotes the recycling of resources.
[0010] The present invention not only improves the performance of grouting materials, but also provides an environmentally friendly and efficient grouting solution, and provides reliable technical support for shield construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a schematic flow diagram of the preparation method of the present invention. Figure 2 It is a schematic diagram of reinforced soil when the unconfined compressive strength is 3d. Figure 3 It is a schematic diagram of reinforced soil when the unconfined compressive strength is 28d. Figure 4 This is a schematic diagram of layer ⑤ of soil. Figure 5 This is a schematic diagram of the seventh layer of soil. DETAILED DESCRIPTION
[0012] The features of the present invention and other related features are further described in detail below in conjunction with the embodiments to facilitate understanding by those skilled in the art:
[0013] A mix ratio for preparing tunnel synchronous grouting slurry using abandoned soil from shield construction in soft soil areas includes the following components in weight percentage: high-quality and environmentally friendly multi-size graded steel slag: 20%-30%, soil: 30%-50%, soft soil special cementitious material: 8.01%-15%, and water: 22.2%-31.49%.
[0014] The steel slag used in this application is refined by the drum process. The drum slag tailings have the characteristics of good stability, excellent particle shape, low iron content, and are easier to use. The processed steel slag has the advantages of low f-CaO, small and uniform particle size, and good slag-steel separation. The steel slag is superior to traditional materials in terms of crushing value, Los Angeles abrasion value, firmness, polishing value and other indicators. Through quality control, the f-CaO content in the steel slag is less than 3%, the metallic iron content is less than 2%, and the heavy metal leaching meets the requirements. It is more suitable for configuring tunnel synchronous grouting slurry. The main chemical composition of the steel slag is shown in Table 1, and the physical properties and safety indicators of the steel slag are shown in Table 2.
[0015] Table 1 Main chemical composition of steel slag (wt, %)
[0016] CaO TFe <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO MnO <![CDATA[P2O5]]> f-CaO 40-46 16-22 9-15 1-3 6-10 4-5 2-3 1-3
[0017] Table 2 Physical properties and safety of steel slag
[0018]
[0019]
[0020] Special soft soil cementitious materials are mineral powder-based curing agents, produced using vertical mill + ball mill + fine mixing process. The main chemical composition is shown in Table 3. Special soft soil cementitious materials overcome the shortcomings of traditional solidified soil, such as the difficulty in continuous distribution of hydration products, low early strength, and insufficient durability, and improve the engineering properties of various soils.
[0021] (1) After the soft soil special cementitious material is mixed with the soil, a hydration reaction occurs to generate a large amount of hydration products such as hydrated calcium silicate and hydrated calcium aluminate, forming a network of stable continuous spatial structures, thereby improving the stability and strength of the soil.
[0022] (2) The soft soil special cementitious material hydrolyzes to form calcium vanadate (AFt) crystals, which convert the free water in the soil into crystallization water, reduce the free water content of the soil, and improve the early strength of the solidified soil.
[0023] (3) In view of the fact that the soil has large pores and can accommodate a large amount of expansion, the soft soil special cementitious material generates an appropriate amount of calcium hydroxide (CH) and AFt expansion components, which expand slightly in the soil and are beneficial to the compaction of its solidified structure.
[0024] (4) The ultrafine and highly active mineral powder components in the soft soil special cementitious materials will produce a volcanic ash reaction under stimulation, thereby strengthening the structural connection between soil particles. At the same time, the finer mineral powder can fill the gaps and improve the density, strength and durability of the soil.
[0025] Figure 2 This is a schematic diagram of the reinforced soil when the unconfined compressive strength is 3d, where the left side is the soil reinforced with traditional curing agent, and the right side is the soil reinforced with special cementitious materials for soft soil; Figure 3 This is a schematic diagram of reinforced soil when the unconfined compressive strength is 28d, where the left side is soil reinforced with traditional curing agent, and the right side is soil reinforced with special cementitious materials for soft soil.
[0026] Table 3 Main chemical components of soft soil special cementitious materials (%)
[0027] CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> MgO <![CDATA[TiO2]]> MnO <![CDATA[SO3]]> 44.35 32.92 13.40 2.58 6.22 0.56 0.42 0.21
[0028] The shield construction spoil is the spoil generated during the shield construction in the soft soil area of Shanghai. Two layers of construction spoil are selected, namely, layer ⑤ (such as Figure 4 As shown) and ⑦ layer soil (as shown Figure 5 The ⑤ layer soil is gray clay, and the ⑦ layer soil is yellow silt. The physical and mechanical properties of the ⑤ layer soil and the ⑦ layer soil are shown in Table 4.
[0029] Table 4 Physical and mechanical properties of spoil
[0030] Soil layer Soil layer name proportion Liquid limit Plastic Limit Plasticity Index ⑤ Layer of soil Clay 2.74 41.5 22.6 18.9 7. Layer of soil Silt 2.70
[0031] Example 1: This example specifically relates to a mix ratio for preparing tunnel synchronous grouting slurry using abandoned soil from shield construction in soft soil areas, and the weight percentage of each component in the mix ratio is as follows: high-quality, environmentally friendly, multi-size graded steel slag: 20.0%, clay: 40.5%, soft soil special cementitious material: 8.0%, and water: 31.5%.
[0032] Example 2: This example specifically relates to a mix ratio for preparing tunnel synchronous grouting slurry using abandoned soil from shield construction in soft soil areas, and the weight percentage of each component in the mix ratio is as follows: high-quality, environmentally friendly, multi-size graded steel slag: 25.0%, clay: 35.6%, soft soil special cementitious material: 8.0%, and water: 31.4%.
[0033] Embodiment 3: The main difference between this embodiment and embodiment 1 is the type of slag, which is silt in this embodiment. The weight percentage of each component in the mix ratio is as follows: high-quality and environmentally friendly multi-size graded steel slag: 21.5%, silt: 45%, soft soil special cementitious material: 8.5%, water: 25%.
[0034] Embodiment 4: The main difference between this embodiment and embodiment 1 is the type of slag, which is silt in this embodiment. The weight percentage of each component in the mix ratio is as follows: high-quality and environmentally friendly multi-size graded steel slag: 25.5%, silt: 35%, soft soil special cementitious material: 8.5%, water: 25%.
[0035] A method for preparing a mix ratio of tunnel synchronous grouting slurry using spoil from shield construction in soft soil areas, which is applicable to the preparation of tunnel synchronous grouting slurry using spoil from shield construction in any one of Examples 1 and 2, specifically comprises the following steps:
[0036] 1) Dry the slag and grind it into fine powder.
[0037] 2) Mix the slag with high-quality, environmentally friendly multi-size graded steel slag and soft soil special cementitious materials according to the mix ratio, put them into a mixer and stir until they are evenly mixed.
[0038] 3) After stirring evenly, add water into the mixer according to the mix ratio and continue stirring until the mud is uniform.
[0039] The grouting liquid obtained by the above preparation method was tested by the following method:
[0040] a) Place the mud into measuring cylinders with a height of 840 ml and measure the water seepage rate of the mud after 2, 4, 6, 8, 10 and 12 hours.
[0041] b) Use the standard method required by GB / T 50080-2016 "Standard Test Method for Performance of Ordinary Concrete Mixtures" to measure the slump of the mud at 0, 2, 4, 6, 8, 10 and 12 hours.
[0042] c) Pour the slurry into cubic test blocks and measure the unconfined compressive strength of the test blocks after 3 days, 7 days, 14 days and 28 days.
[0043] The mix ratio is adjusted based on the experimental results to ensure good performance of the grouting material in shield construction.
[0044] The present invention uses the above preparation method and the mix ratio of Example 1 to prepare a sample.
[0045] After the mud is stirred evenly, the slump and unconfined compressive strength of the mud are tested over time; the test results are shown in Tables 5 and 6. Through the test, it can be seen that the slump and fluidity of the shield tail grouting material can be quickly and effectively improved by adopting the method of this embodiment and the mix ratio of Example 1, which is convenient for construction and ensures the stability of the grouting material; the unconfined compressive strength is improved and the mechanical properties of the grouting material are enhanced.
[0046] Table 5 shows the slump test results.
[0047]
[0048] Table 6 shows the unconfined compressive strength test results.
[0049] time 3d 7d 14d 28d data 0.937Mpa 1.255Mpa 2.124Mpa 2.903Mpa
[0050] The initial setting time of clay is 8 hours and the final setting time is less than 20 hours.
[0051] After the mud is stirred evenly, the slump and unconfined compressive strength of the mud are tested over time; the test results are shown in Tables VII and VIII. Through the test, it can be seen that the slump and fluidity of the shield tail grouting material can be quickly and effectively improved by adopting the method of this embodiment and the mix ratio of Example 2, which is convenient for construction and ensures the stability of the grouting material; the unconfined compressive strength is improved and the mechanical properties of the grouting material are enhanced.
[0052] Table 7 is the slump test results:
[0053]
[0054] Table 8 shows the unconfined compressive strength test results:
[0055] time 3d 7d 14d 28d data 0.825Mpa 1.137Mpa 2.011Mpa 2.613Mpa
[0056] The initial setting time of the clay in Implementation Case 2 is 9 hours, and the final setting time is less than 20 hours.
[0057] The present invention uses the above preparation method and the mix ratio of Example 3 to prepare a sample; as a comparison, 5 control group samples are also prepared using the method of this embodiment, and the mix ratio used in the control group samples is:
[0058] Control group 1: high-quality and environmentally friendly multi-size graded steel slag: 30%, silt: 30%, soft soil special cementitious material: 15%, water: 25%;
[0059] Control group 2: high-quality and environmentally friendly multi-size graded steel slag: 20%, silt: 50%, soft soil special cementitious material: 10%, water: 20%;
[0060] Control group 3: high-quality environmentally friendly multi-size graded steel slag: 24.5%, silt: 45.2%, soft soil special cementitious material: 10.8%, water: 19.5%;
[0061] Control group 4: high-quality environmentally friendly multi-size graded steel slag: 30%, silt: 35%, soft soil special cementitious material: 10%, water: 25%;
[0062] Control group 5: high-quality environmentally friendly multi-size graded steel slag: 25.4%, silt: 45%, soft soil special cementitious material: 8.5%, water: 22.2%.
[0063] After the mud was stirred evenly, the slump, bleeding rate, and unconfined compressive strength of the mud were tested; the test results are shown in Tables 4, 5, and 6. Through the test, it can be seen that the method of this embodiment and the mix ratio of Example 2 can quickly and effectively improve the slump and fluidity of the shield tail grouting material, facilitate construction, control the bleeding rate, ensure the stability of the grouting material, and enhance the mechanical properties of the grouting material. And the effect is significantly better than that of the control portion.
[0064] Table 9 shows the test results of each index of each control group sample:
[0065]
[0066] Table 10 shows the yield strength and 7d unconfined compressive strength test results of the control groups 1 and 5 with better results:
[0067]
[0068] Table 11 is the test results of slump and water bleeding rate of Example 3:
[0069]
[0070] Table 12 is the unconfined compressive strength test results of Example 3:
[0071] time 3d 7d 14d 28d data 0.692Mpa 1.146Mpa 2.003Mpa 2.718Mpa
[0072] The initial setting time of silt is 8 hours and the final setting time is less than 20 hours.
[0073] Table 13 shows the test results of slump and water bleeding rate of Example 4:
[0074]
[0075] Table 14 is the unconfined compressive strength test results of Example 4:
[0076] time 3d 7d 14d 28d data 0.501Mpa 1.032Mpa 1.768Mpa 2.412Mpa
[0077] Based on the above test results, the present invention provides a mix ratio and preparation method for preparing tunnel synchronous grouting slurry using abandoned soil from shield construction in soft soil areas, and optimizes the mix ratio of high-quality and environmentally friendly multi-particle size graded steel slag, soil, soft soil special cementitious material and water through experimental research on clay and silt. The mix ratio of clay is 20.04% of high-quality and environmentally friendly multi-particle size graded steel slag, 40.46% of clay, 8.01% of soft soil special cementitious material, and 31.49% of water; the mix ratio of silt is 21.5% of high-quality and environmentally friendly multi-particle size graded steel slag, 45% of silt, 8.5% of soft soil special cementitious material, and 25% of water. The experimental results show that the slump of clay decreases from 22cm to 10cm within 12 hours, the initial setting time is 8 hours, the unconfined compressive strength is 0.937Mpa at 3 days, 1.255Mpa at 7 days, 2.124Mpa at 14 days, and 2.903Mpa at 28 days; the slump of silt decreases from 28cm to 25cm within 8 hours, the water seepage rate is 2.7% in 2 hours, the unconfined compressive strength is 0.692Mpa at 3 days, 1.146Mpa at 7 days, 2.003Mpa at 14 days, and 2.718Mpa at 28 days. The preparation method includes drying and grinding the slag, mixing it with high-quality, environmentally friendly, multi-size graded steel slag and soft soil special cementitious materials, adding water and stirring evenly, and then conducting water seepage rate, slump and unconfined compressive strength tests. The mixed slag of the present invention not only effectively absorbs the slag that was previously considered to be engineering waste and would cause environmental pollution, but also makes full use of the cementitious properties of high-quality, environmentally friendly, multi-size graded steel slag, significantly improving the fluidity, stability and mechanical properties of the grouting material. This optimized slag mix ratio not only solves the defects of traditional grouting materials, but also provides an environmentally friendly and efficient grouting solution, providing reliable technical support for shield construction.
[0078] The present invention improves the performance of grouting materials by adjusting the slag soil mix ratio, specifically comprising selecting appropriate high-quality and environmentally friendly ratios of multi-size graded steel slag, soil, soft soil special cementitious materials and water, stirring them evenly, conducting tests on slump, water bleeding rate and unconfined compressive strength, optimizing the mix ratio according to the experimental results, and ensuring good performance of the grouting material in shield construction.
Claims
1. A mix ratio for preparing tunnel synchronous grouting slurry using spoil from shield construction in soft soil areas, characterized in that: The invention comprises the following components in weight percentage: multi-size graded steel slag: 20%-30%, slag: 30%-50%, soft soil special cementitious material: 8.01%-15%, and water: 22.2%-31.49%.
2. The mix ratio of the tunnel synchronous grouting slurry prepared by using the spoil from shield construction in soft soil areas according to claim 1 is characterized in that The above-mentioned slag is clay or silt.
3. The mix ratio of the tunnel synchronous grouting slurry prepared by using the spoil from shield construction in soft soil area according to claim 2 is characterized in that The invention comprises the following components in weight percentage: multi-size graded steel slag: 20.04%, clay: 40.46%, soft soil special cementitious material: 8.01%, and water: 31.49%.
4. The mix ratio of the tunnel synchronous grouting slurry prepared by using the spoil from shield construction in soft soil area according to claim 2 is characterized in that The invention comprises the following components in weight percentage: multi-size graded steel slag: 21.5%, silt: 45%, soft soil special cementitious material: 8.5%, and water: 25%.
5. A method for preparing a mix ratio of tunnel synchronous grouting slurry using spoil from shield construction in soft soil areas as described in any one of claims 1 to 4, characterized in that The preparation method comprises the following steps: drying the slag, grinding it into fine powder, mixing it with steel slag with multiple particle sizes and soft soil special cementitious materials according to the mixing ratio, and then putting it into a mixer for stirring. After stirring evenly, continue stirring and add water into the mixer according to the mixing ratio until the mud is stirred evenly.
Citation Information
Patent Citations
Grouting material prepared from steel slag as well as preparation method and application of grouting material
CN112299765A
Steel slag-based double-component high-strength grouting material
CN113636820A
Grouting slurry based on shield muck and industrial solid waste cementing material and preparation method
CN119100727A